Implementasi HMI NB7W-TW00B Pemilah Barang Logam dan Non Logam - Gozy Hermana; Ricky Maulana; Risfendra Risfendra; Juli Sardi (Jurnal Teknik Elektro Indonesia, 2023)
This study aims to facilitate the process of sorting objects made of metal and non-metal so that they can be sorted based on these criteria to the place provided based on a Programmable Logic Controller using the Human Machine Interface as the control center of the tool. Where the Human Machine Interface can be used as a controller and monitor the sorting of objects which is done with two automatic and manual selection methods. Inappropriate program design and use of conventional actuators. The pneumatic system acts as an actuator for sorting goods, namely a double acting cylinder which is installed to push metal and non metal goods towards the conveyor based on what is detected by the capacitive proximity sensor, the cylinder which is installed on the inductive proximity sensor is used to sort metal objects towards storage. If the object is metal, the sensor will detect it and the conveyor will stop and the cylinder will sort the metal object to the metal storage. Non-metal objects will be passed by the sensor to non-metal storage.